Contribution à l'étude de l'activité des huiles essentielles du thym sur des germes pathogènes - Naima,SAYAD; Amal,ACHOU (My University, 2016)
Thyme is an aromatic plant, widespread in Algeria and widely used by local people for its medicinal properties. In this context, the present work focuses on the chemical characterization and study of the antibacterial activity of essential oils extracted from thyme collected from four stations of Souk Ahras Province (North-eastern of Algeria). The steam-distillation of thyme of Sedrata, khddara, Boukabech, and Ouled Drissa gives respective yields of essential oils of 2.08 ± 0.54%, 3.65 ± 0.26%, 1.66 ± 0.37%, and 2.22 ± 0.20%. These yields seem to be very significant for industrial exploitation. Additionally, the qualitative chemical characteristic of these essential oils by thin layer chromatography (TLC) displays the presence of one to five kinds chemical species. Antibacterial potential of essential oils samples of thyme that have been obtained from three regions of Souk Ahras against four bacterial strains reference (Staphylococcus aureus ATCC 43300, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922 et Pseudomonas aeruginosa ATCC 27853) was evaluated by diffusion technique on agar medium. The final results of l’aromatogramme proved that all tested strains are extremely sensitive to thyme essential oils, except that of Pseudomonas Aeruginosaquia which displays some resistance with essential oils of Sedrata and L’Khddara’s thyme............ انضعٍخشة ْٕ َباث عطشي، ٔاعع االَخشاس فً انجضائش ٌٔغخخذو بشكم كبٍش يٍ لبم انغكاٌ انًحهٍٍٍ نخصائصّ انطبٍت. فً ْزا انغٍاق، ٌشكض عًهُا ْزا عهً دساعت انخٕاص انكًٍٍائٍت ٔ انُشاغ انًعاد نهبكخٍشٌا نضٌٕث انعطشٌت انًغخخشجت يٍ انضعٍخشة انخً حى جًعٓا يٍ أسبع يحطاث يٍ ٔالٌت عٕق أْشاط )شًال ششق انجضائش( اعطً انخمطٍش انًائً نُبخت انضعٍخشة يشدٔدا كبٍشا ًٌكٍ اعخغالنّ صُاعٍا حٍث كاٌ يشدٔد كال يٍ يُطمت عذساحت, انخعاسة, بٕكبش ٔ أالد دسٌظ كاالحً %,,,0±8,,2 8,88 ,% ,,81 ±7,1,, % ,,73 ± 6,11 .%,,8, ± باإلظافت إنى رنك، فإٌ انكشف عٍ انغًت انُٕعٍت انكًٍٍائٍت نٓزِ انضٌٕث انعطشٌت عٍ غشٌك كشٔياحٕغشافٍا انطبمت انشلٍمت )CCC )ٌعشض ٔجٕد يشكب انى خًغت يشكباث كًٍٍائٍت غانبٍت يخخهفت. انمذسة انًعادة نهًكشٔباث نضٌٕث األعاعٍت نعٍُاث انضعخش انًأخٕرة يٍ ثالثت يُاغك يٍ عٕق أْشاط ظذ أسبعت إَٔاع يٍ انبكخشٌا انًشجعٍت )succocohahaatS Sctrut CCCC CCCC ahoa sSaouraaoac ,81868 CCCC scuacoaS suuurhahaatS ,077,, 8,188 uu sSutmhdhucS Sccurtuauh CCCC 832,7 )حى حمًٍٓا بٕاعطت حمٍُت انُشش عهً ٔعػ جٍهٕصي َ.خائج االسٔياحٕلشاو اظٓشث أٌ كم انعٍُاث انبكخٍشٌت انًخخبشة كاَج حغاعت نهغاٌت نضٌٕث األعاعٍت نضعٍخشة باعخثُاء sSutmhdhucS curtuauhSc انخً أظٓشث بعط انًمأيت نضٌٕث األعاعٍت نًُطمخً عذساحت ٔ انخعاسة........ Le thym est une plante aromatique, répandue en Algérie et très utilisée par les populations locales pour ses vertus médicinales. Dans ce contexte, le présent travail porte sur la caractérisation chimique et l'étude de l’activité antibactérienne des huiles essentielles extraites des thyms recueillis à partir de quatre stations de la Wilaya de Souk Ahras (Nord-est algérien). L’hydrodistillation des thyms de Sedrata, khddara, Boukabech et d’Ouled Driss a donné les rendements en huiles essentielles respectives de 2,08±0,54 %, de 3,65± 0,26%, de 1,66 ± 0,37 % et de 2,22 ± 0,20%. Ces rendements sont intéressants pour l’exploitation industrielle. La caractérisation chimique qualitative de ces huiles essentielles par CCM a révélé la présence d’une à cinq espèces chimiques majoritaires différentes. Le potentiel antibactérien des huiles essentielles des échantillons du thym de trois régions de Souk Ahras vis-à-vis de quatre souches bactériennes de référence (Staphylococcus aureus ATCC 43300, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922 et Pseudomonas aeruginosa ATCC 27853) a été évalué par la technique de diffusion sur milieu gélosé. Les résultats de l’aromatogramme ont montré que toutes les souches testées ont été extrêmement sensibles aux huiles essentielles des thyms, à l’exception Pseudomonas aeruginosa qui a manifesté une certaine résistance aux huiles essentielles des thyms de Sedrata et de L’Khddara